Chronology from sediment core HZM19, Holzmaar (West-Eifel Volcanic Field, Germany) - García, María Luján; Birlo, Stella; Zahajská, Petra; Wienhues, Giulia; Grosjean, Martin; Zolitschka, Bernd (PANGAEA, 2024)
Chronology is based on Birlo et al. 2023, the Age is in calibrated years Before Present. The sediment core HZM19 was collected in 2019, from Holzmaar, West-Eifel Volcanic Field in Germany using a UWITEC Piston Corer. The sediment core was collected to reconstruct environmental and climate changes of Holzmaar for the last 16,000 years cal BP. Particularly in this data set we cover between 2450-2950 cal BP.
Keywords: Climate changes; lakes; Pigments; Sediments; varves; XRF-core scanning